Relativity of Reschedule and Restructure Products to Non Performing Loan (NPL) Customers at PNM Mekasar Singgahan Branch - Adinda Amelia Fajarwati; Muhammad Nur Abdi (Cita konsultindo, 2024)
Delinquent customers are an obstacle for the debtor to recover the capital provided. As the debtor, PNM Mekaar Singgahan Branch looks for ways from various negotiations for delayed payments to customers or creditors, to giving reprimands or sanctions to customers if the customer has been stuck or affected by a decrease in business income. In order for customers to be free from bankruptcy or default, Restructure and Reschedule products are present. The purpose of the study was to determine the effectiveness of rescheduling and restructuring on NPLs for PNM Mekaar customers in the Singgahan branch. This research uses qualitative methods with data collection techniques through in-depth interviews and correspondent observation, by collecting nominative data for the last 8 weeks. The data collection process was carried out collectively in 5 villages. The results show that reschedule and restructure products have different effectiveness in reducing NPL rates. Restructure products are proven to be more effective in reducing NPL rates compared to reschedule products. This is because restructuring products provide a more comprehensive and sustainable solution for NPL customers.